O Prontuário do Paciente (RECIIS, 2013)
Resenha da obra de Galvão, Maria Cristiane Barbosa; Ricarte, Ivan Luiz Marques. Prontuário do Paciente. Rio de Janeiro: Guanabara Koogan, 2012. ISBN 978-85-2144-8